An exploration of factors influencing adherence to highly active antiretroviral therapy (HAART) among people living with HIV/AIDS in Northern Thailand - Ruanjahn, G.; Roberts, D.; Monterosso, Leanne (Routledge, 2010)
This paper presents the first of a three-phase study exploring the experiences of people living with HIV/AIDS (PLWHA) in Northern Thailand. The principal aim of the study was to gain an in-depth understanding of the factors contributing to adherence in patients taking highly active anti-retroviral therapy (HAART). These insights were used in phase two to inform a number of interventions aimed at improving medication adherence in patients commencing HAART for the first time. The study comprised a cohort of 32 PLWHA over the age of 18 years who had taken HAART for at least three months. Both qualitative and quantitative methods were used. The qualitative component used a multiple case study approach to explore and describe the experiences of patients receiving HAART. The quantitative component comprised the Morisky Medication Adherence Scale and a demographic survey of the respondents. This demographic data were used to provide descriptive statistics of the research population and assist with the interpretation of the qualitative data. The findings identified a number of social, clinical, and economic factors influencing adherence to HAART. These findings led to a number of recommendations that health care providers and policy-makers can implement to improve medication adherence rates in patients taking HAART. The findings demonstrated that improved adherence not only led to improved clinical outcomes, but also the overall quality of life of PLWHA.